CLINICAL AND PHARMACOECONOMICAL EFFICIENCY OF CEFOPERAZONE + SULBACTAM IN CHILDREN, SUFFERING FROM CYSTIC FIBROSIS - E.B. Pavlinova; A.P. Breil'; T.I. Safonova; S.G. Yurovsky (Union of pediatricians of Russia, 2006)
Rational antibacterial therapy of patients, suffering from cystic fibrosis (CF) is one of the urgent problems in pulmonology. In recent years, there has been an increase of resistant strains of microogranisms, which contributes to advance of pulmonary tissue damage and worsens the forecast of a disease. Results of bacterial research among patients, suffering from CF, not only reflect the gravity of a pathological process, but also help the doctors choose the regime of antibacterial therapy. Cefoperazone + sulbactam is a highly active antipseudomonal medication, which is effective in treatment of children, suffering from CF.Key words: cystic fibrosis, children, cefoperazone + sulbactam.